Growth-promoting action and growth factor release by different platelet derivatives. (June 2014) - Passaretti, F.; Tia, M.; D'Esposito, V.; Pascale, M. De; Corso, M. Del; Sepulveres, R.; Liguoro, D.; Valentino, R.; Beguinot, F.; Formisano, P.; Sammartino, G.
Abstract Platelet derivatives are commonly used in wound healing and tissue regeneration. Different procedures of platelet preparation may differentially affect growth factor release and cell growth. Preparation of platelet-rich fibrin (PRF) is accompanied by release of growth factors, including platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF) and transforming growth factor β1 (TGFβ1), and several cytokines. When compared with the standard procedure for platelet-rich plasma (PRP), PRF released 2-fold less PDGF, but >15-fold and >2-fold VEGF and TGFβ1, respectively. Also, the release of several cytokines (IL-4, IL-6, IL-8, IL-10, IFNγ, MIP-1α, MIP-1β and TNFα) was significantly increased in PRF-conditioned medium (CM), compared to PRP-CM. Incubation of both human skin fibroblasts and human umbilical vein endothelial cells (HUVECs) with PRF-derived membrane (mPRF) or with PRF-CM enhanced cell proliferation by >2-fold (p < 0.05). Interestingly, PRP elicited fibroblast growth at a higher extent compared to PRF. At variance, PRF effect on HUVEC growth was significantly greater than that of PRP, consistent with a higher concentration of VEGF in the PRF-CM. Thus, the procedure of PRP preparation leads to a larger release of PDGF, as a possible result of platelet degranulation, while PRF enhances the release of proangiogenic factors.